PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP HASIL BELAJAR DAN AKTIVITAS SISWA SMA - Muslima, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The aims of this research were to find out the students learning outcomes’ and activities differences between the students who were taught by cooperative learning model Think Pair Share and the students who were taught with direct learning model. After that, in this research was conducted the influence of cooperative learning model Think Pair Share toward learning outcomes the eleven grade students of SMAN 1 Tebas on the thermochemical material. The method of this research was quasi experiment. The sample was taken by random sampling technique. Data were analyzed using U-Man Whitney test. The result showed that there are differences in learning outcomes and student activities between those taught by cooperative learning model Think Pair Share and the students who were taught with direct learning model. The use of cooperative learning model Think Pair Share gave influence 27.3% to the improvement of the students learning outcomes. Keywords: think pair share, learning outcomes, activities